2021
DOI: 10.1007/s13178-021-00582-x
|View full text |Cite
|
Sign up to set email alerts
|

Heteronormative Beliefs and Internalized Homonegativity in the Coming Out Process of Portuguese and Turkish Sexual Minority Men

Abstract: Introduction: Studies examining why heteronormative beliefs shape the coming out process of sexual minority men is still scarce. This study aimed to examine whether heteronormative beliefs result in more internalized homonegativity and, in turn, to more sexual identity stigma. We also compared socio-cultural contexts-Portugal and Turkey-with distinct social policies toward sexual minority people. Lastly, we explored the correlates of coming out to friends and family members.Methods: A cross-sectional study wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 97 publications
2
12
0
Order By: Relevance
“…31 These consequences range from changed family dynamics (Goodrich et al, 2019;Jenkins, 2008;Trahan & Goodrich, 2015), to being forced back into a now transparent closet (Béres-Deák, 2011;Kuhar, 2011;Švab, 2016;Švab & Kuhar, 2005 'where a child's homosexual orientation is acknowledged within the family but is not further discussed' (Švab & Kuhar, 2014, p. 19), to homophobic abuse (Alan & Robinson, 2010;Khan & Lowe, 2020) and homelessness (Castellanos, 2016;Tierney & Ward, 2017). 32 Several studies (e.g., de Miguel et al, 2018;Grierson & Smith, 2005;Griffith & Hebl, 2002;Mccormack et al, 2014;Oswald, 1999;Owens, 2017;Torres & Rodrigues, 2021;Wandrey et al, 2015) explore the coming out to family and friends together. Further, friends can become one's family of choice (see Section 3.1.1.).…”
Section: The/a Future?mentioning
confidence: 99%
See 2 more Smart Citations
“…31 These consequences range from changed family dynamics (Goodrich et al, 2019;Jenkins, 2008;Trahan & Goodrich, 2015), to being forced back into a now transparent closet (Béres-Deák, 2011;Kuhar, 2011;Švab, 2016;Švab & Kuhar, 2005 'where a child's homosexual orientation is acknowledged within the family but is not further discussed' (Švab & Kuhar, 2014, p. 19), to homophobic abuse (Alan & Robinson, 2010;Khan & Lowe, 2020) and homelessness (Castellanos, 2016;Tierney & Ward, 2017). 32 Several studies (e.g., de Miguel et al, 2018;Grierson & Smith, 2005;Griffith & Hebl, 2002;Mccormack et al, 2014;Oswald, 1999;Owens, 2017;Torres & Rodrigues, 2021;Wandrey et al, 2015) explore the coming out to family and friends together. Further, friends can become one's family of choice (see Section 3.1.1.).…”
Section: The/a Future?mentioning
confidence: 99%
“… Countries of all inhabited continents are represented within my ‘coming out’ search findings (peer‐reviewed articles or academic books, published in English). For example, in order of their publication date: North America (United States [e.g., Dank, 1971; Fankhanel, 2010; Herdt, 1989; Li & Samp, 2021a; Pastrana et al., 2017; Trahan & Goodrich, 2015), Mexico (e.g., Carrier, 1989), Canada (e.g., Brotman et al., 2002; Kahn & Alessi, 2018), Jamaica (e.g., White et al., 2016), El Salvador (e.g., Thompson & Figueroa, 2020)), Europe (Germany (e.g., Barglowski et al., 2018; Götz & Blanz, 2020; Schafer, 1976), United Kingdom (e.g., Almack, 2007; Clarke & Earley, 2021; Humphrey, 1999; Nordqvist & Smart, 2014; Weeks, 1977), Ireland (e.g., Daly et al., 2020; Neary, 2013; Ryan, 2003; Sharek et al., 2015), Austria (e.g., Bunzl, 2005), Netherlands (e.g., Bannink & Wentink, 2015; Brand, 2005; Maliepaard, 2018), Norway (e.g., Hegna, 2007; Malterud & Bjorkman, 2016), France (e.g., Charbonnier & Graziani, 2016; Provencher, 2011), Hungary (e.g., Béres‐Deák, 2011), Malta (e.g., Bradford & Clark, 2011), Italy (e.g., Benozzo, 2013; Pieri, 2021; Pistella et al., 2020), Portugal (e.g., Costa et al., 2013; Gato et al., 2020; Torres & Rodrigues, 2021), Slovenia (e.g., Kuhar & Švab, 2014; Švab, 2016), Belgium (e.g., Haxhe & D’Amore, 2014), Spain (e.g., de Miguel et al., 2018; Vilanova et al., 2020), Poland (e.g., Barglowski et al., 2018), Romania (e.g., Haxhe et al., 2018), Turkey (e.g., Barglowski et al., 2018…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Minority Stress Model (Meyer, 1995) postulates that individuals from sexual minorities face unique stressors in response to context cues, which is then associated with internalized stigma (for a review, see Rostosky & Riggle, 2017) and poorer health (for a review, see Dürrbaum & Sattler, 2020). Aligned with this reasoning, Torres and Rodrigues (2022) found that gay men who endorsed more heteronormative beliefs (i.e., normative views about the sexuality and sexual behavior of heterosexual individuals) reported more internalized homonegativity (i.e., negative views about gay men). If non-monogamous individuals are met with stigmatization on a daily basis-by being directly confronted with their non-adherence to monogamy or continuously exposed to the expectations of monogamy-then these normative views can also become internalized and have negative consequences for health and well-being.…”
Section: Norms and Internalized Negativitymentioning
confidence: 99%
“…We argue that internalized CNM negativity can also shape perceptions and functioning. For example, internalized negativity has been associated with a negative self-identity (Riggle et al, 2014), discomfort with one's sexual orientation, and fear of coming out (e.g., identity concealment; Dyar et al, 2018;Torres & Rodrigues, 2022). Furthermore, experiencing more internalized negativity has been associated with dehumanization through the form of self-objectification (Haines et al, 2008;see Haslam, 2006) and partner objectification (Szymanski et al, 2019) among sexual minority individuals.…”
Section: Norms and Internalized Negativitymentioning
confidence: 99%